A CHECKLIST OF FREE-LIVING MARINE NEMATODES AT DIFFERENT ECOSYSTEM IN NORTHERN STRAITS OF MALACCA, MALAYSIA - Shakila Samad; Mahadi Mohammad; Sazlina Salleh; Aqilah Darif (Fakultas Biologi | Universitas Jenderal Soedirman, 2018)
Nematodes present in all substrates and sediment types with an enormous number of species. The studies on free-living marine nematodes are still limited in Malaysia. The present study provides general information on genus checklist of free-living marine nematodes in the northern part of Peninsular Malaysia in a different ecosystem which are intertidal zones of estuarine, sandy beach and mangrove ecosystems. Samples were randomly collected at three stations in each ecosystem. A total of 34 genera (22 families and ten suborders) were recorded in three ecosystems. Each ecosystem had common genera which also commonly found worldwide. Viscosia genus was observed in all three ecosystems. The nematode genera of Estuary and mangrove ecosystems had greater similarities than those in the sandy beach.